Lesson Plan Needs for Arabic Essay Writing (Kitabah Hurrah) Using Common European Framework of Reference for Language - Muhammad Kamal Bin Abdul Hakim; Syamsi Setiadi; Shafruddin Tajuddin; Achmad Yani (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
The lesson plan was a stage of instruction that regulates learning activities in the classroom that can have a positive impact on students' abilities in certain subjects. The purpose of this study was to identify the need for lesson plans in essay writing courses through the Common European Framework of Reference for Languages. The study used a qualitative approach through the descriptive method. Participants were students in the 3rd semester of 2020/2021 and lecturer. It was conducted in Arabic Language Education at the State University of Jakarta. Data is taken from the document, interview, and questionnaire. The data analysis process used data reduction, data display, and taking a conclusion. The results show that the lesson plans that have been made still have weaknesses and do not meet the Arabic language mastery standards from the Common European Framework of Reference for Languages ​​(CEFR) standards. However, the results of the study have implications for the level of understanding of the lecturer related to the concept of a lesson plan that must be designed to suit the needs of students, the current situation, and also students' understanding of each mastery of the material being studied.